Diagenesis and fracturing of a large-scale, syntectonic carbonate platform - Arosi, Hamed; Wilson, Moyra (Elsevier Science BV, 2015)
The influence of coeval tectonics on carbonate platform development is widely documented, yet the diagenesis of such syntectonic platforms is barely evaluated. An outcrop, petrographic and geochemical study details here for the first time the diagenesis of the Tonasa Limestone Formation developed in an extensional regime in central Indonesia. This equatorial carbonate system was affected by block faulting, tilt-block rotation, differential uplift and subsidence throughout its Eocene to Early Miocene history (Wilson, 1999; Wilson et al., 2000). The Tonasa carbonate platform is dominated by alteration in shallow to deeper burial depths by fluids with predominantly marine precursor origins. Mechanical and chemical compaction features are common, as are a range of mainly burial-related granular mosaic, blocky and equant calcite cements. Earlier marine cements and meteoric influences are rare, being highly localised to block faulted highs and/or bathymetrically upstanding platform margin areas. Early marine micritisation of allochems was common on the platform top. Tectonic uplift together with a major oceanic throughflow current are thought to be key influences on localised karstification, meteoric diagenesis and marine cementation. The distribution and orientation of faults, fractures and calcite veins together with evidence for their relative timing are the strongest manifestation of tectonism coeval with diagenesis.There is concordance in the orientation and timing of structures affecting the Tonasa Platform with those basin-wide, with the potential for reactivation of pre-existing basement fabrics. Tectonic subsidence, including fault-associated differential subsidence, controlled the degree of burial diagenesis impacting different areas of the platform. A predominance of burial diagenetic features and dearth of earlier marine or meteoric cementation is seen in other Tertiary equatorial platforms and is partly attributed to: (1) predominance of non-framework building larger benthic foraminifera and/or algae that are prone to remobilisation, have low production rates and limited potential to build to sea level, and (2) high runoff due to the equatorial humid climate contributing to lowered marine salinities in SE Asia. Underlying tectonic reasons for the preponderance of a “regional” diagenetic signature over a “syntectonic” one, fracturing excepted, are: (1) development on the flanks of a backarc basin not on typical continental crust, (2) key platform influencing structures are oblique to the main extensional direction in the basin, and (3) development in an overall subsiding tectonic regime, post-dating basin initiation. The aim here is that this study will contribute to understanding diagenetic alteration of syntectonic carbonate platforms, and those from equatorial regions.